Rescue Therapy Using a Rifabutin-Based Regimen is Effective for Cure of Helicobacter pylori Infection - Sander Veldhuyzen van Zanten; Snehal Desai; Linda Best; Geraldine Cooper-Lesins; Dickran Malatjalian; David Haldane; Kevork Peltekian (Canadian Journal of Gastroenterology)
OBJECTIVE: To evaluate the efficacy of rescue therapy using rifabutin, amoxicillin and a proton pump inhibitor (PPI) in the eradication of Helicobacter pylori in patients who have failed at least one course of PPI-based triple therapy.